ChemInform Abstract: Tripod Immobilization of Triphenylphosphane on a Silica‐Gel Surface to Enable Selective Mono‐Ligation to Palladium: Application to Suzuki—Miyaura Cross‐Coupling Reactions with Chloroarenes. Issue 27 (8th July 2014) - Iwai, Tomohiro; Tanaka, Ryotaro; Harada, Tomoya; Sawamura, Masaya
Abstract The new heterogeneous phosphane (POS), which is tripodally immobilized on a silica surface, selectively forms a 1:1 palladium‐ phosphane molecule.